Fetal Mummification in a Holstein Friesian Cow - Ahmad Malik, Asloob; Rana, Sanchi; Singh, Pawanpreet; Naikoo, Mehrajuddin (The Indian Journal of Animal Reproduction, 2025)
A referred case of Holstein Friesian cow in its second parity was presented to the OPD of clinics with the history of vaginal discharge. The case was diagnosed as fetal mummification based on per vaginal followed by per rectal examination and was treated successfully with combination of oestradiol benzoate and cloprostenol sodium injected intramuscularly. On fourth day, a dried brown coloured underdeveloped fetal mass along with dried fetal membranes was expelled out by the animal